A 256 MEMS Membrane Digital Loudspeaker Array Based on PZT Actuators. (2015) - Casset, F.; Dejaeger, R.; Laroche, B.; Desloges, B.; Leclere, Q.; Morisson, R.; Bohard, Y.; Goglio, J.P.; Escato, J.; Fanget, S.
Abstract: This paper reports on the development of a unique Digital Loudspeaker Array solution, based on Pb(Zr0.52, Ti0.48 )O3 (PZT) thin-film actuated membranes, arranged in a matrix and which operate in a binary manner by emitting short pulses of sound pressure. Using the principle of additivity of pressures in the air, it is possible to reconstruct audible sounds. For the first time, electromechanical and acoustic characterizations were reported on 256 MEMS membranes DLA. Sounds audible as far as several meters from the loudspeaker have been generated using low-voltage.